Awareness, Attitude, and Prevalence of usage of magnification devices among the dental practitioners in the state of Andhra Pradesh - A questionnaire-based study - Gautami Subhadra Penmetsa; Loda Princee Mani; Gadde Praveen; Chini Dorai Dwarakanath; S Suresh (Wolters Kluwer Medknow Publications, 2017)
Background: Dentistry, dealing with teeth and supporting tissues in the oral cavity is not only an ever-evolving science but also an art combined with good eye-hand coordination. It not only encompasses clinical and theoretical skills which play a crucial role in the success of therapy but also a lot of intrinsic work is accomplished in dentistry. In a journey to fulfill the above accomplishments and for facilitating early diagnosis of pathologies which usually go unnoticed, a clearer and magnified field of vision are also essential. The purpose of this study is to evaluate the awareness, attitude, and prevalence of the usage of magnification devices among the dental practitioners in the state of Andhra Pradesh. Materials and Methods: A questionnaire-based study was conducted to assess the awareness, attitude, and prevalence of magnification devices among the 370 dental practitioners in Andhra Pradesh. All the participants were provided with a prestructured questionnaire comprising of 24 questions and answering was completely self-based. Results: Among the participants, majority were aware about magnification in dentistry (91.1%), and also of the different types of magnification devices available (90.5%). On the other hand, when the reason for not using magnification devices was taken into consideration, 32.7% attributed that they have not experienced the devices and 32.4% felt that devices were too expensive. Moreover, when regarding the usage of devices was taken into account, only 23.8% of the total participants were exposed to the usage of magnification aids. Conclusion: Among the selected group of participants, even though majority were aware of magnification in dentistry its application in practice was very less.